Health councils as strategies for popular participation in UHS: an integrative review (Research, Society and Development, 2021)
The creation of the Unified Health System (UHS) ensured popular participation - one of the forms being the Health Councils (HC) - in the processes of implementation and inspection of policies aimed at promoting health throughout the country.  The objective of this research was to evaluate how CHs act as participation strategies in the development of the UHS.  This is an integrative review, with data obtained from the literature search using the descriptors: popular participation, single health system and health council;  66 articles were found.  After applying the eligibility and exclusion criteria, 22 articles were selected for analysis, 9 indexed in the BVS database and 13 in SciELO.  It was found that CH  are essential strategy tools, presenting themselves as a direct channel between the population and the development of the UHS,  however, even if in some municipalities their work is being developed in its entirety, some municipalities do not cover all attributions that are the right of the population.  The difficulties encountered by the councils involve a series of causes, ranging from simple lack of interest in their related issues, to more complex issues, such as lack of communication between management and the community, improper infrastructure and lack of financial resources.  Thus, studies that discuss the participation of CH as strategies for popular participation in the UHS are needed to build new strategies that can make planning and participation more effective, active and possible to be carried out across the country.